MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SD NEGERI 1 LAMPASEH MELALUI PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL PADA MATERI OPERASI HITUNG BILANGAN BULAT TAHUN PELAJARAN 2013/2014 - Yunidar Yunidar (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
Teachers have a very important role in growing the students' interest in achieving the certain subject areas including mathematics. For a teacher, it needs to find alternative strategies in growing the students' interest to learn happily (without feeling forced), so it can cause self-confidence to the students, which in turn they can develop the ability that has been there without them knowing it. In contextual learning the teacher does not require students to memorize facts but the teacher should encourage the students to construct their own knowledge. Through the contextual learning model the students are expected to learn through 'experience' rather than 'memorize'. In learning, the teachers need to understand the initial conceptions what the students have and relate to the concepts to be studied. This study aims to know the increasing of the Students’ Learning Outcomes of Class VI Elementary School 1 Lampaseh through the Application of Contextual Learning on Counting Integers Operation Model Year 2013/2014. The type of the research is a Classroom Action Research which includes planning, action, observation, reflection or evaluation. The approach used in this study is student oriented with the quantitative data obtained from the test of learning outcomes and qualitative data obtained through the observation sheet and questionnaire which was given to the students to know the students' responses. This research is descriptive research, which is to know the increasing of the students’ ability in determining material of counting integer operation model by using observation sheet, test sheet, and interview. The results of this study indicate that through the use of contextual learning model can improve the students’ learning outcomes in Mathematics on the subject of counting integers operation. This is shown from the average grade point in the first cycle is 61.875, while the students’ achievement is 54.83% and the second cycle is 87.1, and the students’ achievement is 87.5%. Besides, it is also seen from the number of the students who get grades under the KKM. In cycle I there are 11 students and in cycle II, it reduced to 5 students.